In good shape?: a comparative evaluation of the registration of 3D product forms as trade marks and designs under EU law - Chave, Lynne (2018)
The thesis seeks to develop a normatively well-grounded and practically viable framework for the registration of product shapes under EU design and trade mark law, taking proper account of doctrinal overlaps. The institutional challenge is to develop a model which avoids unnecessary duplication of protection while permitting each regime to function in a principled and complementary manner.